Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2020
DOI: 10.1111/jfb.14243
|View full text |Cite
|
Sign up to set email alerts
|

Amazonian invaders in an Asian biodiversity hotspot: Understanding demographics for the management of the armoured sailfin catfish, Pterygoplichthys pardalis in Kerala, India

Abstract: Invasion of armoured catfish, Pterygoplichthys spp., is a major threat to global aquatic biodiversity, and developing effective strategies for their control and eradication is both a concern and a research priority. A length-based population assessment of invasive Pterygoplichthys pardalis in southern India, a hotspot for endemic aquatic biodiversity, indicated that rapid growth, high growth performance index and continuous recruitment have aided their successful invasion. Increasing fishing pressure on the ad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 18 publications
0
10
0
Order By: Relevance
“…Studies by Raj et al (2019) and Roshni et al (2020) have shown that two invasive species P. pardalis and C. gariepinus, which have established healthy populations in the waterbodies of the SWG, can be managed only by targeting smallersized individuals rather than large adult fish; rapid growth rate, low fishing mortality and continuous recruitment contributes to the invasion success of the two species. The impact of P. reticulata, which has established even in many second-order streams of SWG, can be revealed only through detailed studies on invasion biology, as previous research indicate their strong invasion potential and impact on aquatic biodiversity (Sievers et al, 2012;El-Sabaawi Rana et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Studies by Raj et al (2019) and Roshni et al (2020) have shown that two invasive species P. pardalis and C. gariepinus, which have established healthy populations in the waterbodies of the SWG, can be managed only by targeting smallersized individuals rather than large adult fish; rapid growth rate, low fishing mortality and continuous recruitment contributes to the invasion success of the two species. The impact of P. reticulata, which has established even in many second-order streams of SWG, can be revealed only through detailed studies on invasion biology, as previous research indicate their strong invasion potential and impact on aquatic biodiversity (Sievers et al, 2012;El-Sabaawi Rana et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, a number of introduced non-native ornamental fish are plying in aquarium trade and pet keeping (Singh et al, 2013b;Sandiliyan, 2016). As a result, several introduced non-native species of aquaculture and aquarium are now available in open waters including the forest reserves, protected areas and even coastal areas Lakra, 2011, Singh et al, 2013a;Sandilyan, 2016;Raj et al, 2019;Chakraborty et al, 2020;.…”
Section: Introductionmentioning
confidence: 99%
“…This, coupled with the availability of plenty of detritus in the polluted drainages as food, provide them with a competitive edge over indigenous species, better reproductive strategies, including the ability to breed in burrows along the stream banks and crevices in the granite walls, accessory respiratory organs, batch spawning abilities and parental care assisted P. pardalis to colonize the system successfully. The population assessment of P. pardalis from the same habitat indicated that rapid growth, high growth performance index, and continuous recruitment are the reasons for their successful invasion, and targeting the young individuals would help in controlling the population of the invasive fish (Raj et al 2020). We recommend more research on the invasion biology of invasive P. pardalis, incorporating long-term studies to fully understand the long-term strategies for their establishment and plasticity in the reproductive behaviour.…”
mentioning
confidence: 99%
“…Based on the results of this work, it may be presumed that P. pardalis inhabiting the natural drainages without noticeable temperature variations is a batch spawner and temperature may not be an important limiting factor for spawning of fish that live in a habitat with stable or less fluctuating water temperature. The population assessment of P. pardalis from natural drainages of Thiruvananthapuram indicated rapid growth, high-performance index and continuous recruitment, which resulted in their successful invasion (Raj et al 2020). Maximum reproductive activity of P. disjunctivus and L. multiradiatus were reported from July to September (Liang et al 2005;Rueda-Jasso et al 2013).…”
mentioning
confidence: 99%